One pathway, many products - Fischbach, M. A.; Clardy, J.
Biosynthetic pathways for secondary metabolites usually make many products, not just one. In this Commentary, we consider why molecular promiscuity might be an evolutionarily advantageous feature of these pathways.
Keywords: BIOSYNTHETIC PATHWAYS; SECONDARY METABOLITES